Implicaturas conversacionais: violação das máximas nos depoimentos de lula no contexto da lava-jato - OLIVEIRA, Raquelinhe Carneiro de (2019)
The present work aims to analyze how the violation of conversational maxims occurs in Lula 's testimonies to Judge Sergio Moro, and what effects of meaning (implicatures) are generated from these violations. For this, we focus our studies on the Theory of Implicatures, the Principle of Cooperation (PC) and the Conversational Maxims of the philosopher Herbert Paul Grice (1975; 1982), which states that behind an affirmative there is almost always something "implicit" (implicature), therefore, the author updates the implicatures by means of four conversational maxims: Quantity, Quality, Relevance and Mode. Thus, we will use as corpus of analysis two testimonies of the Brazil’s ex-president Luís Inácio Lula da Silva, in the context of the Lava Jato operation, to Judge Sergio Moro, aiming analyze how cognitive processes occur (inference and implicature), violation of conversational maxims and the PC between the interlocutors of a real communicative interaction.